Role of post‐operative radiation boost for soft tissue sarcomas with positive margins following pre‐operative radiation and surgery. Issue 7 (11th August 2014) - Pan, Elizabeth; Goldberg, Saveli I.; Chen, Yen‐Lin; Giraud, Christine; Hornick, Jason L.; Nielsen, Gunnlaugur P.; Hornicek, Francis J.; Raut, Chandrajit P.; DeLaney, Thomas F.; Baldini, Elizabeth H.
<x xml:space="preserve">Abstract</x> Background and Objectives The role of a radiation therapy (RT) boost for positive margins following pre‐operative RT and surgery in extremity soft tissue sarcomas (STS) is unclear. We assessed the contribution of a boost to local control (LC), disease‐free survival (DFS), and overall survival (OS). Methods We identified 67 patients treated from 1987 to 2011 with pre‐operative RT and surgery with positive margin(s). Select patients received a boost delivered as peri‐operative Iridium‐192 brachytherapy (BRT), intra‐operative electrons (IORT), or post‐operative external beam RT (EBRT). Results Ten patients received no RT boost, 10 received a BRT or IORT boost, and 47 received an EBRT boost. Five‐year LC rates for no boost, BRT/IORT boost, and EBRT boost were 100%, 78%, and 71% (P = 0.5). On multivariate analysis, there were no significant predictors for LC. Variables associated with improved DFS rates were single positive margin (P = 0.007) and low tumor grade (P = 0.03). Tumor size <5 cm (P = 0.003), low grade (P = 0.001), and boost (P = 0.02) were associated with longer survival. Conclusions We did not identify a LC advantage for an RT boost. Given the unidentified selection factors for delivery of boost and its potential toxicities, its role in this setting remains unproven. J. Surg. Oncol. 2014 110:817–822. © 2014 Wiley Periodicals, Inc.